2008
DOI: 10.1016/j.jjcc.2008.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Coronary endarterectomy in the left anterior descending artery

Abstract: Coronary endarterectomy of the LAD with a patch plasty using the LITA is associated with acceptable mortality, morbidity, and angiographic patency. CVFR measured by transthoracic echocardiography showed a favorable functional status in the endarterectomized LAD. Endarterectomy is considered to be one of the available surgical methods for patients with a diffusely diseased LAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 18 publications
2
51
0
4
Order By: Relevance
“…Many studies have evaluated graft patency after CE, and the patency rate has been reported as occurring in 80-98.6% of cases [14,19,20]; these studies report on the mid-term or long-term patency from coronary angiography (CAG). In this study there was an attempt to evaluate the midterm patency of CE, but postoperative computed tomographic angiography (CTA) was performed in only 58% of the patients.…”
Section: Oncab-cementioning
confidence: 99%
“…Many studies have evaluated graft patency after CE, and the patency rate has been reported as occurring in 80-98.6% of cases [14,19,20]; these studies report on the mid-term or long-term patency from coronary angiography (CAG). In this study there was an attempt to evaluate the midterm patency of CE, but postoperative computed tomographic angiography (CTA) was performed in only 58% of the patients.…”
Section: Oncab-cementioning
confidence: 99%
“…Несомненный интерес представляют результаты исследования, опубликованного Takanashi S. et al [12]. Авторы ретроспективно изучили результаты 148 открытых эндартерэктомий из ПМЖА.…”
Section: Discussionunclassified
“…Furthermore, it can be settled to secure the distal portion of artery following an intimal dissection of the coronary artery happens. 2 In the close method, coronary endarterectomies were performed manually by slow sustain and continuous traction of atheroma trailed by reproduction with anastomosis with pre-planned graft. 2,23 Two synchronous arteriotomy can be used for coronary endarterectomy to make the framework rapid and reduce ischemic time.…”
Section: How To Perform Ce?mentioning
confidence: 99%
“…2 In the close method, coronary endarterectomies were performed manually by slow sustain and continuous traction of atheroma trailed by reproduction with anastomosis with pre-planned graft. 2,23 Two synchronous arteriotomy can be used for coronary endarterectomy to make the framework rapid and reduce ischemic time. 24 The close method is shorter in duration and the graft anastomosis is easier than open method.…”
Section: How To Perform Ce?mentioning
confidence: 99%
See 1 more Smart Citation